Contemporary Encounters with Ancient Metaphysics - Greenstine, Abraham (Edinburgh University Press, 2017)
Like the ancient inquiries into the nature of things, contemporary continental realism and materialism, from Deleuze to the Speculative Realists, embraces a commitment to investigate beings, without subordinating it to analyses of language, consciousness, texts or the social.This pensée brute, traditionally known as metaphysics, dares to question the one and the many, the potential and the actual, the material and immaterial and the world itself. This apparent kinship is not merely thematic, since contemporary thinkers explicitly and repeatedly return to the texts and figures of the Greco-Roman world. In this volume, leading philosophers address these varied, volatile, and novel interactions and themselves contribute to reconceiving and redeploying the problems of ancient metaphysics. Alongside this are 2 original and previously unpublished translations of essays by Gilles Deleuze and Pierre Aubenque.